Dual-scale porous/grooved microstructures prepared by nanosecond laser surface texturing for high-performance vapor chambers. (January 2022) - Long, Jiangyou; Chu, Pingchuan; Li, Yan; Lin, Jinghao; Cao, Zuo; Xu, Meifang; Ren, Qinglei; Xie, Xiaozhu
Abstract: A vapor chamber (VC) is a two-phase device used to spread heat in two dimensions, which is widely used in high heat flux applications such as the cooling of high-power chips and light-emitting diodes. The wicks inside a VC greatly affect the device performance, which is commonly prepared by sintering metal powders or fibers. Herein, we directly prepare the wick structures on copper substrates by nanosecond laser surface texturing and investigate the thermal performance of the prepared VCs. We find that both dual-scale porous structures with a porosity of ~68% and deep V-shaped microgrooves with an aspect ratio of 3.5 can be fabricated on copper substrates by nanosecond laser surface texturing. The former shows a high capillary pumping pressure and the latter shows a high permeability. When employing the optimal structures as the wicks, the prepared 2 mm thick VC shows a minimum thermal resistance of 0.137 °C/W under a heat load of 120 W. Our results provide a novel technique to prepare wick structures used in high-performance VCs, which avoids the sintering process and may be used for the manufacturing of ultrathin VCs.